Dietary grape pomace extract supplementation improved meat quality, antioxidant capacity, and immune performance in finishing pigs - Tian, Xuekai; Li, Dong; Zhao, Xin; Xiao, Zitong; Sun, Jingchun; Yuan, Tiantian; Wang, Yongcheng; Zuo, Xinhui; Yang, Gongshe; Yu, Taiyong (Frontiers in Microbiology, 2023)
In pig production, reducing production costs and improving immunity were of importance. Grape pomace as a good agriculture by-production, has been thrown away as food waste in a long time. Recently, we found it could be used as a new source of pig feed. We investigated the effect of grape pomace on inflammation, gut barrier function, meat quality and growth performance in finishing pig. Our result showed treatment samples significantly decreased in water loss, IL-1β, DAO, ROS and MDA content (p<0.05). The IgA, IgG, IgM, CAT, T-AOC, SOD and IFN-γ significantly increased compared with the control samples (p<0.05). Meanwhile, the relative mRNA expression of tight junction protein occludin showed a significant difference (p<0.05). Analysis of metagenomic sequencing indicated that grape pomace significantly decreased the relative abundance of Treponema and Strptococcus (p<0.05). In summary, our results demonstrated that grape pomace could improve meat quality, alleviate inflammation and decrease oxidative stress.